Being A Positive Bystander: Male Antiviolence Allies' Experiences Of "Stepping Up" - Casey, Erin A.; Ohler, Kristin (Journal Of Interpersonal Violence, 2011)
As bystander approaches become increasingly prevalent elements of sexual and domestic violence prevention efforts, it is necessary to better understand the factors that support or impede individuals in taking positive action in the face of aggressive or disrespectful behavior from others. This study presents descriptive findings about the bystander experiences of 27 men who recently became involved in antiviolence against women work. More specifically, we describe the consistency with which respondents actively intervene in the speech or behavior of others, the strategies they use, and the factors they weigh as they deliberate taking action. Respondents report a complex and interrelated set of individual and contextual influences on their choices within bystander opportunities, which hold implications for both violence-specific models of bystander behavior and for prevention intervention development.